Alteration of extracellular matrix proteins in atrophic periodontal ligament of hypofunctional rat molars - Daneeya Na Nan; Vincent Everts; Joao N. Ferreira; Vorapat Trachoo; Thanaphum Osathanon; Nuttha Klincumhom; Prasit Pavasant (Nature Publishing Group, 2023)
Abstract Objectives The aim of this study was to investigate the effect of mechanical force on possible dynamic changes of the matrix proteins deposition in the PDL upon in vitro mechanical and in vivo occlusal forces in a rat model with hypofunctional conditions. Materials and methods Intermittent compressive force (ICF) and shear force (SF) were applied to human periodontal ligament stem cells (PDLSCs). Protein expression of collagen I and POSTN was analyzed by western blot technique. To establish an in vivo model, rat maxillary molars were extracted to facilitate hypofunction of the periodontal ligament (PDL) tissue of the opposing mandibular molar. The mandibles were collected after 4-, 8-, and 12-weeks post-extraction and used for micro-CT and immunohistochemical analysis. Results ICF and SF increased the synthesis of POSTN by human PDLSCs. Histological changes in the hypofunctional teeth revealed a narrowing of the PDL space, along with a decreased amount of collagen I, POSTN, and laminin in perivascular structures compared to the functional contralateral molars. Conclusion Our results revealed that loss of occlusal force disrupts deposition of some major matrix proteins in the PDL, underscoring the relevance of mechanical forces in maintaining periodontal tissue homeostasis by modulating ECM composition.